Web application development on supply chain data visualization - Yee, Wei Min (Nanyang Technological University, 2021)
This Final Year Project focuses on the development of two projects related to supply chain end-to-end visibility. The student developed a KPI dashboard in Project 1 - Proof of Concept of Digital Twin for Next Generation Supply Chain and a supply chain map-based interactive interface in Project 2 - Supply Chain Visualization on Map. Both projects are developed to be displayed in Manufacturing Intelligence Control Room (MICR) in Advanced Remanufacturing and Technology Centre (ARTC) to showcase the future potential of a Supply Chain Digital Twin solution.